Preparation method of amphiphilic polymer modified by magnetic particles

The amphiphilic azo polymer is prepared by synthesizing intermediates and using Lys(z)-NCA ring-opening polymerization method, and combined with carboxy modified magnetic nanoparticles by co-precipitation method, solving the challenge of binding magnetic nanoparticles with azo micelles in the prior art, achieving efficient and accurate drug delivery effect.

CN119552372APending Publication Date: 2025-03-04LIAONING UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411718918.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing magnetic nanoparticles and azo micelle binding technology faces the challenges of surface modification and chemical coupling design in practical applications, and the magnetic field guidance efficiency is limited, which affects the drug delivery effect.

Method used

The intermediate 4-((4-aminophenyl)diazalyl)benzoic acid was synthesized and a hydrophobic end azo polymer was obtained by Lys(z)-NCA ring-opening polymerization method, and then an amphiphilic azo polymer was obtained by polyethylene glycol lipidation reaction. Then, a regular spherical magnetic particle modified polymer was prepared by co-precipitation method of carboxyl modified magnetic nanoparticles and amphiphilic azo polymer.

Benefits of technology

The stable combination of magnetic nanoparticles and azo polymer is achieved, forming a regular spherical product, with good dispersion, improving the efficiency and accuracy of drug delivery, and enhancing the targeting and functional diversity of the carrier.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552372A_ABST
    Figure CN119552372A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of polymer self-assembly, and particularly relates to a preparation method of a magnetic particle modified amphiphilic polymer. The carboxyl-modified magnetic nanoparticles prepared by the invention are connected with an amphiphilic azo polymer, 4-vinylbenzoic acid is added to functional groups of the magnetic nanoparticles by molecular self-assembly, and the preparation method is simple. The carboxyl-modified magnetic particle amphiphilic azo polymer disclosed by the invention is in a regular sphere shape, and is uniform in size and good in dispersity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer self-assembly, and in particular relates to a method for preparing an amphiphilic polymer modified by magnetic particles. Background Art

[0002] Magnetic nanoparticles are a kind of functional material with superparamagnetism, usually made of ferrite (such as Fe3O4) or other metal oxides, and have excellent magnetic response characteristics. Combining magnetic nanoparticles with amphiphilic azo polymer micelles can form a multifunctional nano drug carrier system. This system achieves directional drug delivery through magnetic field control, and at the same time utilizes the stimulus responsiveness of the azo group to further enhance the temporal and spatial precision of drug release. Magnetic nanoparticles give azo micelles the ability to respond to external magnetic fields, thereby achieving precise control of the drug delivery location, opening up new possibilities for tumor treatment and targeted drug delivery.

[0003] Magnetic nanoparticles have good biocompatibility and controllability, and play an important role in drug delivery. Guided by an external magnetic field, these nanoparticles can quickly gather at tumors or other specific lesions, greatly increasing the local concentration of the drug while reducing the side effects of systemic distribution. After combining with azo micelles, magnetic nanoparticles can act as a "positioning device" for the carrier, inducing the delivery of drugs carried by the micelles to targeted tissues through magnetic field induction. The azo group releases the drug under external stimulation (such as light or pH changes), thus forming a highly controllable and synergistic drug release system.

[0004] Azo polymer micelles themselves have stimulus response properties such as light, heat and enzymes, and can achieve precise drug release under specific microenvironments. The introduction of magnetic nanoparticles into the azo micelle system further enhances the targeting and functional diversity of the carrier. For example, under the dual stimulation of light and magnetic field, the azo group can undergo rapid chemical cleavage to release the encapsulated drug, while the magnetic nanoparticles ensure that the micelles are aggregated in the targeted area. This synergistic effect not only improves the drug delivery efficiency, but also significantly reduces the nonspecific toxicity of drugs to healthy tissues, making it show broad application prospects in fields such as tumor treatment. Although the combination technology of magnetic nanoparticles and azo micelles has great potential, it still faces some challenges in practical applications. First, the surface modification of magnetic nanoparticles and the chemical coupling of azo micelles need to be precisely designed to ensure their stability and functionality in a physiological environment. Second, the efficiency of magnetic field guidance is limited by the ability of magnetic field to penetrate deep tissues of the human body, which may affect the effect of drug delivery. In addition, the metabolites of magnetic nanoparticles and azo polymers need to be comprehensively evaluated for toxicity and biocompatibility to ensure their safety. Future research should focus on optimizing material structure, developing efficient synthesis processes, and exploring in vivo and in vitro synergistic mechanisms to lay the foundation for the clinical transformation of this multifunctional nanoplatform.

[0005] Functionalized magnetic nanomaterials are a new type of composite material that has developed rapidly in recent years. As a type of magnetic nanomaterial with a small particle size and a large specific surface area, it is very suitable as a carrier. When combined with substances carrying different functional structures, functionalized magnetic nanoparticles have broad application prospects in the fields of drug transportation, enzyme immobilization, selective enrichment, and wastewater purification. Summary of the invention

[0006] The purpose of the present invention is to overcome the defects of the prior art and provide a method for preparing a magnetic nanoparticle modified polymer. The intermediate 4-((4-aminophenyl)diazenyl)benzoic acid is synthesized and a hydrophobic end azo polymer is obtained by a Lys(z)-NCA ring-opening polymerization method and then subjected to a polyethylene glycol esterification reaction to obtain an amphiphilic azo polymer; an azo polymer micelle is prepared by an organic solvent evaporation method; and magnetic nanoparticles are prepared by a coprecipitation method.

[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0008] A method for preparing an amphiphilic polymer modified with magnetic particles comprises the following steps:

[0009] 1) Synthesis of carboxyl-modified magnetic nanoparticles: Dissolve ferric chloride hexahydrate and ferrous chloride tetrahydrate in deionized water in a beaker, heat to 40°C and stir until dissolved, cool to room temperature and set aside; add the above two solutions to a flask and set the temperature to 70°C, while introducing nitrogen and slowly dripping concentrated ammonia under mechanical stirring, quickly add anhydrous ethanol mixed with oleic acid, and continue to react for 1 hour; after the reaction, wash three times with anhydrous ethanol and deionized water, separate the magnetic nanoparticles with a magnet, and dry them in a vacuum drying oven at 50°C; then take the magnetic nanoparticles and 4-vinylbenzoic acid, add them to deionized water, ultrasonically disperse them, put them in a water bath and let them stand for 3 hours; take potassium persulfate and dissolve it in deionized water, slowly add it to the magnetic nanoparticle solution along the wall of the beaker, continue to stand for polymerization reaction, stop the reaction after 2 hours, and then wash the products separated by the magnet with anhydrous ethanol and deionized water alternately, and place the washed magnetic nanoparticles in a vacuum drying oven at 60°C for 2 hours to obtain carboxyl-modified magnetic nanoparticles;

[0010] 2) Synthesis of carboxyl-modified magnetic particles linked to amphiphilic azo polymers: The carboxyl-modified magnetic nanoparticles prepared in step 1) and the amphiphilic azo polymers were added to a three-necked flask, and DMF was added as a reaction solvent, and mechanical stirring was applied. When the solvent temperature reached 35°C, catalysts 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 4-dimethylaminopyridine were added to react for 48 hours. After the reaction, the target product was separated by magnetic adsorption and washed three times with anhydrous ethanol to obtain the target product.

[0011] Furthermore, in the above preparation method, in step 1), 5.00 g of ferric chloride hexahydrate and 2.00 g of ferrous chloride tetrahydrate are dissolved in 10 mL of deionized water respectively.

[0012] Furthermore, in the above preparation method, in step 1), the amount of concentrated ammonia water used is 10 mL; the anhydrous ethanol mixed with oleic acid contains 1 mL of oleic acid and 10 mL of anhydrous ethanol.

[0013] Furthermore, in the above preparation method, in step 1), the amount of the magnetic nanoparticles is 10 mg, the amount of 4-vinylbenzoic acid is 40 mg, and the amount of potassium persulfate is 8 mg.

[0014] Furthermore, in the above preparation method, in step 2), the amount of carboxyl-modified magnetic nanoparticles is 10 mg, the amount of amphiphilic azo polymer is 40 mg, the amount of DMF is 50 mL, and the amounts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 4-dimethylaminopyridine are each 20 mg.

[0015] Furthermore, in the above-mentioned preparation method, in step 2), the preparation method of the amphiphilic azo polymer comprises the following steps:

[0016] 1) Synthesis of 4-((4-aminophenyl)diazenyl)benzoic acid: dissolve p-aminobenzoic acid in deionized water, add concentrated hydrochloric acid and stir for 20 minutes, and cool in an ice bath after stirring; dissolve sodium nitrite in deionized water, and cool the dissolved sodium nitrite solution in an ice bath, maintaining the temperature at 0-5°C; slowly drop the cooled sodium nitrite solution into the p-aminobenzoic acid aqueous solution in the ice bath, and react for 15 minutes; filter the solution after the reaction, retain the filtrate and store it in an ice bath; take another large beaker, dissolve sodium acetate and aniline sulfite in deionized water, maintain the solution temperature at 0-5°C, then drop the filtrate into the large beaker, stir for 1 hour, adjust the pH to maintain acidity, filter and dry; after drying, react with sodium hydroxide solution at 90°C for 3 hours, finally adjust the solution pH to 6 in an ice bath, filter and dry, and obtain 4-((4-aminophenyl)diazenyl)benzoic acid;

[0017] 2) Synthesis of hydrophobic azo polymer: N6-Cbz-L-lysine dissolved in THF was added to a round-bottom flask and stirred for 15 minutes. Triphosgene dissolved in THF was slowly added dropwise to the round-bottom flask for reaction for 2 hours. The solution after the reaction was added to n-hexane and refrigerated overnight. The white solid Lys(z)-NCA was obtained by suction filtration and vacuum drying. The dried white solid Lys(z)-NCA and 4-((4-aminophenyl)diazenyl)benzoic acid obtained in step 1) were dissolved in DMF and stirred at room temperature for 36 hours to form a yellow solution. Anhydrous ethanol was then added to the yellow solution and stirred. The yellow solid obtained by suction filtration and drying was the hydrophobic azo polymer.

[0018] 3) Synthesis of amphiphilic azo polymer: The hydrophobic azo polymer obtained in step 2) is dissolved in DMF, polyethylene glycol is added to the solution, and the mixture is stirred at room temperature for 30 minutes. After the solid is dissolved, catalyst 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 4-dimethylaminopyridine are added to react at 35° C. for 48 hours. After the reaction is completed, the solution is dialyzed three times, and finally lyophilized to obtain a yellow solid, which is the amphiphilic azo polymer.

[0019] Furthermore, in the preparation method of the above-mentioned amphiphilic azo polymer, in step 1), the amount of p-aminobenzoic acid is 13.7 g, the amount of concentrated hydrochloric acid is 33.6 mL, the amount of sodium nitrite is 6.9 g, the amount of sodium acetate is 60 g, the amount of aniline sulfite is 21.1 g, and the sodium hydroxide solution is 15 g of sodium hydroxide dissolved in 50 mL of deionized water.

[0020] Furthermore, in the preparation method of the above-mentioned amphiphilic azo polymer, in step 2), the amount of N6-Cbz-L-lysine is 6 g, the amount of triphosgene is 2 g, the amount of 4-((4-aminophenyl)diazenyl)benzoic acid is 0.18 g, the amount of Lys(z)-NCA is 5.2 g, and the volume of n-hexane is 500 mL.

[0021] Furthermore, in the preparation method of the above-mentioned amphiphilic azo polymer, in step 3), the amount of the hydrophobic azo polymer used is 3.6 g, the amount of polyethylene glycol used is 1.776 g, and the molecular weight of the polyethylene glycol is 2000 Mv; the amount of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 4-dimethylaminopyridine used is 0.5 g each.

[0022] Furthermore, in the above method for preparing the amphiphilic azo polymer, in step 3), the dialysis uses a dialysis bag with a molecular weight cutoff of 3000Da.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] 1. The carboxyl-modified magnetic nanoparticles of the present invention utilize molecular self-assembly to add 4-vinylbenzoic acid to the functional groups of the magnetic nanoparticles and the preparation method is simple.

[0025] 2. The carboxyl-modified magnetic particles connected to the amphiphilic azo polymer of the present invention have a regular spherical shape with uniform size and good dispersibility. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 1 is a structural diagram of the amphiphilic azo polymer prepared in Example 1.

[0027] Figure 2 The infrared absorption spectra of (a) amphiphilic azo polymer, (b) carboxyl-modified magnetic nanoparticles, and (c) carboxyl-modified magnetic nanoparticles linked to amphiphilic azo polymers prepared in Examples 1 and 2 are shown.

[0028] Figure 3 This is a transmission image of the carboxyl-modified magnetic nanoparticles prepared in Example 2. DETAILED DESCRIPTION

[0029] In order to further understand the present invention, the preferred experimental scheme of the present invention is described below in conjunction with embodiments, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the requirements of the present invention.

[0030] Example 1 Preparation of amphiphilic azo polymer

[0031] 1) Synthesis of 4-((4-aminophenyl)diazenyl)benzoic acid: 13.7 g of p-aminobenzoic acid was dissolved in 30 mL of deionized water, and 33.6 mL of concentrated hydrochloric acid was added and stirred for 20 minutes. After stirring, the mixture was cooled in an ice bath. 6.9 g of sodium nitrite was weighed and dissolved in 10 mL of deionized water. The dissolved sodium nitrite solution was cooled in an ice bath and the temperature was maintained at 0-5°C. The cooled sodium nitrite solution was slowly added dropwise to the p-aminobenzoic acid solution in the ice bath and reacted for 15 minutes. The solution after the reaction was extracted and Filter, retain the filtrate and store it in an ice bath; take another large beaker, dissolve 60g of sodium acetate and 21.1g of aniline sulfite in 25mL of deionized water, keep the solution temperature at 0-5°C, then add the filtrate dropwise to the large beaker and stir for 1 hour, adjust the pH to maintain acidity, filter and dry; after drying, react with sodium hydroxide solution (15g of sodium hydroxide dissolved in 50mL of deionized water) at 90°C for 3 hours, finally adjust the solution pH to 6 in an ice bath, filter and dry to obtain 4-((4-aminophenyl)diazenyl)benzoic acid.

[0032] 2) Synthesis of a hydrophobic azo polymer: 6 g of N6-Cbz-L-lysine dissolved in 50 mL of THF was added to a round-bottom flask and stirred for 15 minutes. 2 g of triphosgene dissolved in 50 mL of THF was slowly added dropwise to the round-bottom flask and reacted for 2 hours. The reaction solution was added to 500 mL of n-hexane and refrigerated overnight. The white solid Lys(z)-NCA was obtained by suction filtration and vacuum drying. 5.2 g of the dried Lys(z)-NCA and 0.18 g of 4-((4-aminophenyl)diazenyl)benzoic acid obtained in step 1) were dissolved in DMF and stirred at room temperature for 36 hours to form a yellow solution. Anhydrous ethanol was then added to the yellow solution and stirred. The yellow solid obtained by suction filtration and drying was the hydrophobic azo polymer.

[0033] 3) Synthesis of amphiphilic azo polymer: 3.6 g of the hydrophobic azo polymer obtained in step 2) was dissolved in 50 mL of DMF, and 1.776 g of polyethylene glycol (molecular weight 2000 Mv) was added to the solution, and stirred at room temperature for 30 minutes. After the solid was dissolved, 0.5 g of catalyst 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 4-dimethylaminopyridine were added, and the mixture was reacted at 35° C. for 48 hours. After the reaction was completed, the solution was dialyzed three times (using a dialysis bag with a molecular weight cutoff of 3000 Da), and finally freeze-dried to obtain a yellow solid, which was an amphiphilic azo polymer (whose structural formula is as follows: Figure 1 ).

[0034] Example 2 Preparation of carboxyl-modified magnetic particles linked to amphiphilic azo polymers

[0035] 1) Synthesis of carboxyl-modified magnetic nanoparticles: 5.00 g of ferric chloride hexahydrate and 2.00 g of ferrous chloride tetrahydrate were weighed and dissolved in 10 mL of deionized water in a 100 mL beaker, heated to 40°C and stirred until dissolved, cooled to room temperature and set aside; the two solutions were added to a flask and the temperature was set to 70°C, and 10 mL of concentrated ammonia was slowly added dropwise under nitrogen gas mechanical stirring, and anhydrous ethanol mixed with oleic acid (1 mL of oleic acid and 10 mL of anhydrous ethanol) was quickly added, and the reaction was continued for 1 hour; after the reaction was completed, the magnetic particles were washed three times with anhydrous ethanol and deionized water, and then separated with a magnet and dried in a vacuum drying oven at 50°C; then 10 mg of magnetic nanoparticles and 40 mg of 4-vinylbenzoic acid was added to deionized water, ultrasonically dispersed for 20 minutes, and then placed in a water bath for 3 hours; 8 mg of potassium persulfate was weighed and dissolved in 10 mL of deionized water, and slowly added to the magnetic particle solution along the wall of the beaker, and the polymerization reaction was continued to proceed. The reaction was stopped after 2 hours, and then the product separated by a magnet was alternately washed with anhydrous ethanol and deionized water, and the washed magnetic particles were placed in a vacuum drying oven at 60°C for 2 hours to obtain carboxyl-modified magnetic nanoparticles;

[0036] 2) Synthesis of carboxyl-modified magnetic particles linked to amphiphilic azo polymers: 10 mg of carboxyl-modified magnetic nanoparticles prepared in step 1) and 40 mg of amphiphilic azo polymers were added to a three-necked flask, 50 mL of DMF was used as the reaction solvent, and mechanical stirring was added. When the solvent temperature reached 35°C, 20 mg each of catalyst 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 4-dimethylaminopyridine were added and reacted for 48 hours. After the reaction, the target product was separated by magnetic adsorption and washed three times with anhydrous ethanol to obtain the target product.

[0037] Figure 2 The infrared absorption spectra of (a) amphiphilic azo polymer, (b) carboxyl modified magnetic nanoparticles, and (c) carboxyl modified magnetic nanoparticles linked to amphiphilic azo polymers prepared in Examples 1 and 2 are shown. Figure 2 It can be seen that the wavelength of curve (b) is 1700cm -1 The appearance of carboxyl absorption peaks on the left and right proves that the magnetic particles are connected to carboxyl groups, and the appearance of ether bond absorption peaks on curve (c) proves that the magnetic particles are connected to polymer micelles.

[0038] Figure 3 is a transmission image of the carboxyl-modified magnetic nanoparticles prepared in Example 2. Figure 3 It can be seen that the magnetic particles are uniform in size, with a diameter of about 10 nm.

[0039] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some or all of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing an amphiphilic polymer modified with magnetic particles, characterized in that: The steps include: 1) Synthesis of carboxyl-modified magnetic nanoparticles: Dissolve ferric chloride hexahydrate and ferrous chloride tetrahydrate in deionized water in a beaker, heat to 40°C and stir until dissolved, cool to room temperature and set aside; add the above two solutions to a flask and set the temperature to 70°C, while introducing nitrogen and slowly dripping concentrated ammonia under mechanical stirring, quickly add anhydrous ethanol mixed with oleic acid, and continue to react for 1 hour; after the reaction, wash three times with anhydrous ethanol and deionized water, separate the magnetic nanoparticles with a magnet, and dry them in a vacuum drying oven at 50°C; then take the magnetic nanoparticles and 4-vinylbenzoic acid, add them to deionized water, ultrasonically disperse them, put them in a water bath and let them stand for 3 hours; take potassium persulfate and dissolve it in deionized water, slowly add it to the magnetic nanoparticle solution along the wall of the beaker, continue to stand for polymerization reaction, stop the reaction after 2 hours, and then wash the products separated by the magnet with anhydrous ethanol and deionized water alternately, and place the washed magnetic nanoparticles in a vacuum drying oven at 60°C for 2 hours to obtain carboxyl-modified magnetic nanoparticles; 2) Synthesis of carboxyl-modified magnetic particles linked to amphiphilic azo polymers: The carboxyl-modified magnetic nanoparticles prepared in step 1) and the amphiphilic azo polymers were added to a three-necked flask, and DMF was added as a reaction solvent, and mechanical stirring was applied. When the solvent temperature reached 35°C, catalysts 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 4-dimethylaminopyridine were added to react for 48 hours. After the reaction, the target product was separated by magnetic adsorption and washed three times with anhydrous ethanol to obtain the target product.

2. The preparation method according to claim 1, characterized in that: In step 1), 5.00 g of ferric chloride hexahydrate and 2.00 g of ferrous chloride tetrahydrate were dissolved in 10 mL of deionized water respectively.

3. The preparation method according to claim 1, characterized in that: In step 1), the amount of concentrated ammonia water is 10 mL; the anhydrous ethanol mixed with oleic acid contains 1 mL of oleic acid and 10 mL of anhydrous ethanol.

4. The preparation method according to claim 1, characterized in that: In step 1), the amount of the magnetic nanoparticles is 10 mg, the amount of 4-vinylbenzoic acid is 40 mg, and the amount of potassium persulfate is 8 mg.

5. The preparation method according to claim 1, characterized in that: In step 2), the amount of carboxyl-modified magnetic nanoparticles is 10 mg, the amount of amphiphilic azo polymer is 40 mg, the amount of DMF is 50 mL, and the amounts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 4-dimethylaminopyridine are each 20 mg.

6. The preparation method according to claim 1, characterized in that: In step 2), the preparation method of the amphiphilic azo polymer comprises the following steps: 1) Synthesis of 4-((4-aminophenyl)diazenyl)benzoic acid: dissolve p-aminobenzoic acid in deionized water, add concentrated hydrochloric acid and stir for 20 minutes, and cool in an ice bath after stirring; dissolve sodium nitrite in deionized water, and cool the dissolved sodium nitrite solution in an ice bath, maintaining the temperature at 0-5°C; slowly drop the cooled sodium nitrite solution into the p-aminobenzoic acid aqueous solution in the ice bath, and react for 15 minutes; filter the solution after the reaction, retain the filtrate and store it in an ice bath; take another large beaker, dissolve sodium acetate and aniline sulfite in deionized water, maintain the solution temperature at 0-5°C, then drop the filtrate into the large beaker, stir for 1 hour, adjust the pH to maintain acidity, filter and dry; after drying, react with sodium hydroxide solution at 90°C for 3 hours, finally adjust the solution pH to 6 in an ice bath, filter and dry, and obtain 4-((4-aminophenyl)diazenyl)benzoic acid; 2) Synthesis of hydrophobic azo polymer: N6-Cbz-L-lysine dissolved in THF was added to a round-bottom flask and stirred for 15 minutes. Triphosgene dissolved in THF was slowly added dropwise to the round-bottom flask for reaction for 2 hours. The solution after the reaction was added to n-hexane and refrigerated overnight. The white solid Lys(z)-NCA was obtained by suction filtration and vacuum drying. The dried white solid Lys(z)-NCA and 4-((4-aminophenyl)diazenyl)benzoic acid obtained in step 1) were dissolved in DMF and stirred at room temperature for 36 hours to form a yellow solution. Anhydrous ethanol was then added to the yellow solution and stirred. The yellow solid obtained by suction filtration and drying was the hydrophobic azo polymer. 3) Synthesis of amphiphilic azo polymer: The hydrophobic azo polymer obtained in step 2) is dissolved in DMF, polyethylene glycol is added to the solution, and the mixture is stirred at room temperature for 30 minutes. After the solid is dissolved, catalyst 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 4-dimethylaminopyridine are added to react at 35° C. for 48 hours. After the reaction is completed, the solution is dialyzed three times, and finally lyophilized to obtain a yellow solid, which is the amphiphilic azo polymer.

7. The preparation method according to claim 6, characterized in that: In step 1), the amount of p-aminobenzoic acid is 13.7 g, the amount of concentrated hydrochloric acid is 33.6 mL, the amount of sodium nitrite is 6.9 g, the amount of sodium acetate is 60 g, the amount of aniline sulfite is 21.1 g, and the sodium hydroxide solution is 15 g of sodium hydroxide dissolved in 50 mL of deionized water.

8. The preparation method according to claim 6, characterized in that: In step 2), the amount of N6-Cbz-L-lysine is 6 g, the amount of triphosgene is 2 g, the amount of 4-((4-aminophenyl)diazenyl)benzoic acid is 0.18 g, the amount of Lys(z)-NCA is 5.2 g, and the volume of n-hexane is 500 mL.

9. The preparation method according to claim 6, characterized in that: In step 3), the amount of the hydrophobic azo polymer used is 3.6 g, the amount of polyethylene glycol used is 1.776 g, and the molecular weight of the polyethylene glycol is 2000 Mv; the amount of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 4-dimethylaminopyridine used is 0.5 g each.

10. The preparation method according to claim 6, characterized in that: In step 3), the dialysis uses a dialysis bag with a molecular weight cutoff of 3000Da.